Resilience of wheat crop production in selected war zones in Afghanistan - Noor, Stanikzai Ahmad (2020)
Wheat is the staple food crop in Afghanistan, and maintaining its production plays an important role in ensuring food security and food self-sufficiency. However, being a country that has been facing war since 1978, it has been challenging for the wheat production industry to maintain its production to feed its people. In order to be resilient in their operations and grow in the face of war, players in this industry may have to withstand, survive and adapt to a different situation and phenomena within the conflict and war conditions as compared to the regular wheat production context in the peaceful countries. Hence, this study aimed to investigate the resilience, vulnerabilities, and capabilities of the wheat crop production players in a prolonged war zone. This study is conducted through the case study approach. Required data was collected through interviews, observations and documents. Twenty-three informants, including individual farmers, cooperative members, and extension officers were selected and interviewed using the snowballing technique. Collected data was analyzed through thematic analysis. In order to analyze collected data, this study employed Pettit et al., (2010) resilience framework. The study found that wheat crop farmers possess the status of balanced resilience in some points while the farmers have the status of unbalanced resilience in other parts. Furthermore, this study found that farmers are vulnerable to lack of extension and credit services, inaccessibility to input/output markets, property destruction, lack of storage facilities, and lack of agriculture technologies/ machinery in the war zone. In addition, wheat crop industry players in the war zone have to face psychological effects and financial corruption as well. Besides that, the study also revealed that farmers possess some specific capabilities that enable them to withstand, adapt and continue wheat crop production in war conditions. These specific capabilities include; ability in using traditional technologies, inputs exchange, community farmers’ assistance, sourcing inputs from multiple sources, and multi-usage of inputs in a war zone. Based on findings, this study recommends the provision of extension and credit services, inputs subsidies, agriculture machinery, and advanced agriculture technologies to farmers. The government have to create some channels through which farmers can access input/output markets. Building of underground storages is recommended because this will enable farmers to protect their produces from destruction in war conditions. The government must eradicate financial corruption that has adversely affected wheat crop production. Lastly, the government should support creation of farmers’ cooperative through which farmers act independently and self-sufficiently. This study has practical and theoretical contribution to the wheat crop industry as well as the current body of knowledge in the field of resilience. In the practical part, this study highlighted several unbalanced resilience areas that can be prioritized in the agriculture policy-making. In the theoretical part, this study revealed new information regarding the vulnerability and capability of wheat crop farmers in a war zone. The study found several new constructs to the resilience framework of Pettit et al. (2010) which can further explain the production of crops especially in a war/conflicts zone.